2016
DOI: 10.1007/s11517-016-1504-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of accuracy of fall detection algorithms (threshold-based vs. machine learning) using waist-mounted tri-axial accelerometer signals from a comprehensive set of falls and non-fall trials

Abstract: Falls are the leading cause of injury-related morbidity and mortality among older adults. Over 90 % of hip and wrist fractures and 60 % of traumatic brain injuries in older adults are due to falls. Another serious consequence of falls among older adults is the 'long lie' experienced by individuals who are unable to get up and remain on the ground for an extended period of time after a fall. Considerable research has been conducted over the past decade on the design of wearable sensor systems that can automatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
107
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(108 citation statements)
references
References 33 publications
1
107
0
Order By: Relevance
“…The experimental results showed that their proposed method has low computational complexity and is robust among embedded systems. Khojasteh et al [25] compared the performance of threshold-based algorithms and various machine learning algorithms in detecting falls, using data from waist-located tri-axial accelerometers. The experimental results showed that the machine learning algorithms outperformed the threshold-based algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…The experimental results showed that their proposed method has low computational complexity and is robust among embedded systems. Khojasteh et al [25] compared the performance of threshold-based algorithms and various machine learning algorithms in detecting falls, using data from waist-located tri-axial accelerometers. The experimental results showed that the machine learning algorithms outperformed the threshold-based algorithms.…”
Section: Related Workmentioning
confidence: 99%
“…However, to detect weather a fall occurred relies on the performance of the detection mechanism. The most common and simplest fall detection is the threshold method [8]. Nevertheless, the performance heavily depends on the fixed threshold level.…”
Section: Corresponding Authormentioning
confidence: 99%
“…Hence, it is rarely used alone, and often combined with other machine learning methods such as decision tree (DT) [9], [10], artificial neural networks (ANN) [11], hidden Markov model (HMM) [12] and Support Vector Machine (SVM) [4], [14], [15] can be combined to outperform the threshold method [8], [14]. Among the machine learning methods, SVM was found the most robust for fall detection when compared to other methods such as threshold-based methods and the decision tree method [8]. However, most works which deploy SVM for fall detection use time-series features [8], [16].…”
Section: Corresponding Authormentioning
confidence: 99%
See 1 more Smart Citation
“…The authors used directly the acceleration values and the signal magnitude area as features. In [3], five threshold-based algorithms and five machine learning algorithms were compared. The overall performance of the machine learning algorithms was greater.…”
mentioning
confidence: 99%